Pengaruh Kas Neto Yang diperoleh Dari Aktivitas Operasi Terhadap Laba Tahun Berjalan - Eka Sari Ningsih (Universitas Malahayati, 2014)
Cash flow statement is a statement that is useful for managers, investors, creditors and other users are able to provide an overview to determine the cause of the change in the amount of cash or to determine the sources and uses of cash during a certain period Net cash provided by operating activities was supposed to provide information about how much the company's ability to generate income. The objective of research in this thesis is to determine whether there was an effect of net cash provided by operating activities of the incomet for the year. Data collection techniques using secondary data in the form of annual financial statements of PT Indofood Sukses Makmur Tbk from 2003 to 2013. The analysis tool used is a simple regression analysis. These results indicate that partial hypothesis testing based on the obtained value oft is greater than t table (1.705 <2.228) or by looking at the significant level of 0.122, the value is greater than the value of a (0.05) or (0.122> 0 , 05), then the hypothesis Ho is accepted and Ha is rejected, the net cash provided by operating activities do not affect the incomet for the year. From this analysis it can be concluded that the company has the effect of net cash provided by operating activities were positive but not significant, the company noted that the increase in operating activities is higher than the increase in the percentage of the profit generated by operating activities. It can be concluded from these data that the company was not able to create an efficient level of net income through the company's operations.